Metformin Alleviates Airway Hyperresponsiveness in a Mouse Model of Diet-Induced Obesity - Gu, Chenjuan; Loube, Jeff; Lee, Rachel; Bevans-Fonti, Shannon; Wu, Tianshi David; Barmine, Jessica H.; Jun, Jonathan C.; McCormack, Meredith C.; Hansel, Nadia N.; Mitzner, Wayne; Polotsky, Vsevolod Y. (Frontiers in Physiology, 2022)
Obese asthma is a unique phenotype of asthma characterized by non-allergic airway hyperresponsiveness (AHR) and inflammation which responds poorly to standard asthma therapy. Metformin is an oral hypoglycemic drug with insulin-sensitizing and anti-inflammatory properties. The objective of the current study was to test the effect of metformin on AHR in a mouse model of diet-induced obesity (DIO). We fed 12-week-old C57BL/6J DIO mice with a high fat diet for 8 weeks and treated them with either placebo (control, n=10) or metformin (n=10) added in drinking water (300mg/kg/day) during the last 2 weeks of the experiment. We assessed AHR, metabolic profiles, and inflammatory markers after treatments. Metformin did not affect body weight or fasting blood glucose, but significantly reduced serum insulin (p=0.0117). Metformin reduced AHR at 30 mg/mL of methacholine challenge (p=0.0052) without affecting baseline airway resistance. Metformin did not affect circulating white blood cell counts or lung cytokine mRNA expression, but modestly decreased circulating platelet count. We conclude that metformin alleviated AHR in DIO mice. This finding suggests metformin has the potential to become an adjuvant pharmacological therapy in obese asthma.